2019
DOI: 10.1021/acs.jced.9b00680
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Amines: A Critical Analysis of the Experimental Enthalpies of Formation by Comparison with Theoretical Calculations

Abstract: The accuracy of experimental data on enthalpies of formation and vaporization of aliphatic amines (primary, secondary, and tertiary amines, di-, tri-, and tetramines, and cycloalkylamines) was assessed by theoretical calculations. The gas-phase enthalpies of formation were calculated using the Gaussian 4 (G4) method combined with isodesmic reactions. Three amines, CH 3 NH 2 , CH 3 NHCH 3 , and (CH 3 ) 3 N, were used as the main reference species in the isodesmic reactions; their experimental enthalpies of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Unless explicitly said to the contrary, the recent literature study [41] will likewise always be used as the source of information for the enthalpy of formation of acyclic amines. In particular, we accept their recommended value of −76 kJ/mol for the enthalpy of formation of diethylamine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unless explicitly said to the contrary, the recent literature study [41] will likewise always be used as the source of information for the enthalpy of formation of acyclic amines. In particular, we accept their recommended value of −76 kJ/mol for the enthalpy of formation of diethylamine.…”
Section: Resultsmentioning
confidence: 99%
“…For the tertiary N-methylaziridine, the secondary 2-methylaziridine, and the primary cyclopropylamine, the enthalpies of formation are 120, 89 and 77 kJ/mol, respectively. [39,41] As a general rule, we find the isomerization transformation [Eq (21)] of isostructural tertiary to secondary to primary amines is exothermic, of increasingly N-alkylated to C-alkylated amines, by ca. 20 kJ/mol.…”
Section: Hcnc ! Ccnh (21)mentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] are mentioned in the Supplementary Materials.…”
mentioning
confidence: 99%
“…show that the proposed DLPNO−CCSD(T)-based atom equivalents methodology is more efficient than the G4 method. In our previous studies of amines, amino acids, hydrazines, azides, ureas, nitro compounds, and phenols (see Reference [26] and references therein) it was shown that the G4 method, especially combined with isodesmic reactions, can give reliable theoretical estimates of the gas-phase enthalpies of formation. At the same time, for polycyclic adamantane T A B L E 1 Experimental and theoretical enthalpies of formation (kJ/mol) of adamantane and molecules of norbornadiene cycle we could not get a good agreement with the experiment either for atomization or isodesmic reaction.…”
mentioning
confidence: 99%